Urbanização turística e paisagem: o caso do município de Salinópolis - SOUZA, Deiliany Lima de (2018)
The tourism from the decade of 1970 passed to be glimpsed like an important economical alternative for many Brazilian cities, from this period the urbane interventions intensify like the form of marketing of the city, when the public power was harnessed to that it starts to preoccupy with the spread of an image of favorable city the practice of the tourism. This work is ruled in the relation tourist urbanization and scenery, trying to point out the process of use of the city like commodity. In Salinópolis, this process is shown up from the urbane interventions turned to improve the development of the tourism in the city. In this perspective, the object of this monographic work consists in identifying the principal investments in tourist urbanization, trying to identify aspects on the image of the city of Salinópolis, after the introduction of these investments, rescuing part of his history and his development while tourist destiny. In the present work focuses the paper of the tourism like agent transformer of the spaces, detaching the paper of the State like the supporting lever of this process. A descriptive study of character was carried out exploratory in the intention of investigating the current dynamic one of the tourism in the city. Besides, collection of data was carried out in public organs made a list to the tourism in Salinópolis and analysis of the plans, programs and projects of tourist development. The inquiry demonstrated that the public power uses the interventions tourist for institutionalize the image of the city. In this sense, It Borders works as Complex of the Blowpipe and Urbanization of the Beach of Lookout post, which they are constantly a destiny of the tourist investments, they are used like speeches that turn privileged pieces of the urbane space into representative areas of the urbane totality.